Transient transfection of Cryptosporidium baileyi. Issue 6 (December 2017) - Tetens, A.-K.; Hanig, S.; Kurth, M.; Greif, G.; Entzeroth, R.
Abstract: Here we demonstrate the transient transfection of C. baileyi . We describe the transfection of this apicomplexan parasite and the cultivation in ovo . The functionality of heterologous sequences in C. baileyi was demonstrated by the expression and detection of the mCherry protein in ovo . The mCherry protein was expressed in parasitic stages up to the oocyst stage under the control of the heterologous promoter region of the C. parvum actin gene.